Efeito do clima nas características e propriedades da madeira de um clone de Eucalyptus urophylla - Almeida, Maria Naruna Felix de (2021)
The climate contributes to the growth and development of wood cells, as it interferes with the ecophysiology of the plant, its growth and accumulation of biomass. Considering the extension of Brazilian territory, with marked edaphoclimatic differences, the expansion of forest boundaries and the diversity of results on the influence of climatic variables on the properties of eucalyptus wood, this thesis aimed to evaluate and compare the properties and characteristics of the most eucalyptus clone planted in Brazil (E. urophylla) due to climatic differences between 12 sites along the Brazilian longitudinal gradient. The characteristics of the evaluated wood were: wood density (WD), heartwood percentage (H%) and heartwood and sapwood density (HD and SD), anatomical elements of the xylem (area (VA) and frequency of vessels (VF), fiber wall thickness (FWT) and fiber lumen diameter (FLD) and chemical composition of wood (extractives, lignin, syringyl / guaiacyl ratio (S / G) and ash, CHNS and mineral elements). Absolute values of the variables average air temperature (T), precipitation (P), and soil water deficit (SWD) per site, referring to each year of cultivation and average of six years, were used for comparison. The dendrometric variables mean annual increment (MAI) and increment in cycle volume (ICV) were also used. The means were compared by the Scott-Knott test. Pearson's correlation and linear regression analysis were used to verify the influence of climate on wood characteristics. The most humid sites, located in greater latitudes, presented the highest values of H% (between 61 and 67%). In general, heartwood density was lower than sapwood density, with sites with the lowest MAI values showing the lowest SD values, and wet sites with higher MAI the highest densities. H% showed strong and significant correlations with T, P, SWD, and MAI, while WD showed moderate and significant correlations only with T, MAI and water use efficiency. The influence of climate on the density of E. urophylla wood occurred mainly after the 20 months of tree growth, when WD was mainly correlated with T (r> 0.6). The 1 ° C increase in T resulted in a WD reduction of 0.014 g cm-3 , and increases of 10 m³ ha-1 in the final volume were related to an increase of 0.004 g cm-3 in WD. The density spatialization showed a trend towards a positive density gradient from the north to the south of Brazil. Temperature was again the variable that showed the highest correlations, now with the wood anatomical characteristics. Among sites, climatic differences were more accentuated than between cycles, which led to better correlations between climate and final averages of wood characteristics. Temperature showed strong and negative correlations with WD, VA and FTW (r = -0.89, r = -0.75 and r = -0.83) and positive with VF and FLD (r = 0.62, r = 0, 84). Total lignin, holocellulose and ash do not present significant differences between sites. In the elementary analysis, site 33, which is more humid, differed from the others, with higher content of carbon and hydrogen, and lower values of oxygen. Only the total lignin and S / G ratio showed significant correlations with the meteorological variables, with drier sites presenting a higher S / G ratio. Regarding the quantification of mineral elements, higher levels of one element did not necessarily mean high levels of the others and less productive sites exported less elements per hectare. In general, E. urophylla clone expressed its best phenotype in sites with climatic conditions closest to the conditions for which it was improved, and the choice of the site proved to be a more important factor than the fluctuations in the climate in each location.